2015
DOI: 10.1039/c5ce00685f
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis, crystallisation, and thin-film processing of single crystals of trans-[Ru(SO2)(NH3)4(H2O)][p-TolSO3]2 bearing SO2 linkage photo-isomers: towards optical device applications

Abstract: Metastable sulfur dioxide linkage photo-isomers can be generated in a family of ruthenium tetraamminebased complexes in their single-crystal form; this imparts them with attractive prospects as holographic data storage media (dark state = 0; photo-isomer state = 1). Embedding these optically encoded single crystals into thin-film technology via a polymer host should present one possible option for their ultimate device application. Crystals of trans-ijRuIJSO 2 )IJNH 3 ) 4 IJH 2 O)]ijp-TolSO 3 ] 2 IJ[Ru]-SO 2 ) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Photocrystallography has an important and notable history in the characterization of metastable linkage isomers of transition metal complexes containing NO, SO 2 , and NO 2 – , but its beginnings arise from irradiation of cinnamic acid to effect [2+2] cycloadditions, which continues today. , Coppens led the way in these studies on sodium nitroprusside. , Separately, Cole has uncovered synergistic motions inside crystals of [Ru­(NH 3 ) 4 ­(X)­SO 2 ] n + (X is typically an anionic or neutral ligand trans to SO 2 ), where the S-bonded SO 2 yields both η 2 -SO 2 - and O-bonded isomers upon irradiation of single crystals. , The relatively close packing of each Ru cation appears to cause other nearby cations to rotate. In this way, photonic energy is transduced to mechanical energy inside the crystal, reminiscent of a rotor .…”
Section: Correlating Electronic Structural Changes With Atomic Struct...mentioning
confidence: 99%
“…Photocrystallography has an important and notable history in the characterization of metastable linkage isomers of transition metal complexes containing NO, SO 2 , and NO 2 – , but its beginnings arise from irradiation of cinnamic acid to effect [2+2] cycloadditions, which continues today. , Coppens led the way in these studies on sodium nitroprusside. , Separately, Cole has uncovered synergistic motions inside crystals of [Ru­(NH 3 ) 4 ­(X)­SO 2 ] n + (X is typically an anionic or neutral ligand trans to SO 2 ), where the S-bonded SO 2 yields both η 2 -SO 2 - and O-bonded isomers upon irradiation of single crystals. , The relatively close packing of each Ru cation appears to cause other nearby cations to rotate. In this way, photonic energy is transduced to mechanical energy inside the crystal, reminiscent of a rotor .…”
Section: Correlating Electronic Structural Changes With Atomic Struct...mentioning
confidence: 99%
“…1 Photo-switching between linkage isomers can be achieved in both solution and the solid-state, with irradiation of the solid leading to the production of a metastable state (MS) isomer below some critical temperature. 2 In situ photocrystallographic studies have to-date revealed the structures of various MS linkage isomers, including nitrosyl, 3,4 nitrite, [5][6][7][8] sulfur dioxide, [9][10][11] and di-nitrogen 12 systems.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by the in situ reaction of trans -[Ru­(NH 3 ) 4 (SO 2 )­Cl]Cl and p -toluenesulfonic acid in the PVA matrix and an in situ precipitating crystallization. Transmission electron microscopy, diffraction, and UV–vis spectroscopy indicated that the photoactivated linkage isomerization was uncompromised by inclusion in polymer thin films . The size of the crystallites was optimized within the polymer, having dimensions between 1 and 10 μm.…”
Section: Photocrystallographic Studies On Nitrosyl and Sulfur Dioxide...mentioning
confidence: 99%
“…Because of the relationship that we have established between temperature and lifetime in these linkage isomers, they should be useful benchmark materials as time-resolved diffraction methodology continues to develop. The successful incorporation of some of the nitrosyl and sulfur dioxide linkage isomers into polymers and xerogels without the loss of their switching function , suggests that these systems may have optical device applications. Schaniel et al have shown that it is possible to write short-lived phase gratings with identically and orthogonally polarized waves using nanosecond laser pulses in crystals of iron nitrosyl complexes.…”
Section: Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation